Pharmacogenetics of testosterone replacement therapy. (August 2009) - Zitzmann, Michael
Variable phenotypes of androgen insensitivity exist in humans, mainly owing to defective, mutated androgen receptors. A more subtle modulation of androgen effects is related to the CAG repeat polymorphism ([CAG]n) in exon 1 of the androgen receptor gene, in vitro, transcription of androgen-dependent target genes is attenuated with increasing length of triplets. As a clinical entity, the CAG repeat polymorphism can relate to variations of androgenicity in (apparently) eugonadal men in various tissues and psychological traits, the longer the (CAG)n, the less prominent the androgen effect when individuals with similar testosterone concentrations are compared. A strictly defined threshold to hypogonadism is likely to be replaced by a continuum spanned by genetics as well as symptom specificity. In addition, effects of externally applied testosterone can be markedly influenced by the (CAG)n and respective pharmacogenetic implications are likely influence indications as well as modalities of testosterone treatment of hypogonadal men.